ANALISIS MARKETING MIX PRODUK JAJANAN KHAS BIMA SEBAGAI UPAYA MEMPERTAHANKAN KULINER LOKAL DI KABUPATEN BIMA - Sri Ernawati; Alya Pratiwi; Ahmad Bani Adam (Jurnal PenKoMi : Kajian Pendidikan dan Ekonomi, 2025)
The marketing mix, which consists of elements such as product, price, place, and promotion, plays a key role in attracting consumers' attention and influencing their purchasing decisions. Typical food, which often reflect local culture and traditions, have great potential to attract consumer interest. Overall, implementing an effective marketing mix for typical food products can increase the attractiveness and sales of the product. This research aims to analyze the Marketing Mix of Bima Typical food Products as an Effort to Maintain Local Culinary. This type of research is descriptive quantitative with data collection from observations, questionnaires with a Likert scale, and literature study. Data analysis techniques use validity tests, reliability tests, one sample t-tests with the help of SPSS v 2023. The results of the research show that the marketing mix for Bima specialty food products is an effort to maintain local culinary delights above the criteria that have been set at 75% (Good)